P254 Utilising community empowerment and biometrics to improve tuberculosis treatment outcomes in Delhi's slum population: the Op ASHA model. (12th November 2015) - Pan, D; Lee, E; Lock, L; Batra, R; Abubakar, I; Batra, S; Lipman, M
Abstract : Introduction: India accounts for more than one-fifth of the total global tuberculosis (TB) incidence. In response, the Revised National TB Control Program (RNTCP) of India has supported the decentralisation of service delivery with encouragement of active community participation. Operation ASHA is an international NGO that offers TB services to slum populations – a group that have proven difficult historically to engage. It employs a unique treatment approach involving community-based providers and biometric data registration to support adherence. We report treatment outcome for patients with presumed drug-susceptible tuberculosis managed by Op ASHA within Delhi's slum districts. Methods: Retrospective, observational cohort study focusing on patients within 14 southern Delhi slum districts started on treatment according to RNTCP guidelines between 1.4.2012 and 31.3.2013. Demographic and clinical information were systematically recorded. Patients still on treatment by the end of October 2013 were excluded from analysis. Successful outcomes were defined as bacteriologically confirmed cure or treatment completion. Adverse outcomes were: treatment default, conversion to MDR-TB treatment, treatment failure or death. Results: 1217 patients were started on treatment. 29% were aged <20; and 42% were female. 52% had pulmonary TB; of these 55% were sputum smear positive (58% grade II or III out of III). 218 (18%) subjects re-treated for TB were excluded from further outcome analysis. The remaining 999 patients had similar clinical characteristics to the whole study population. Successful outcome after 6 months of treatment was recorded in 85% of subjects (77% pulmonary, 91% extrapulmonary cases). Adverse outcomes were recorded in 16% of those with pulmonary TB. This was considerably less common in extrapulmonary TB, where it was recorded in only 6%. Death was reported in 3% of pulmonary and 1% of extrapulmonary patients. Conclusions: The model of care achieves the WHO target for treatment completion of 85% in a population considered very high risk of failure under traditional TB programmes. Future work needs to focus on the factors that result in adverse outcomes, in particular for the key patient population with infectious pulmonary TB.